Resurgence and Waldschmidt constant of the ideal of a fat almost collinear subscheme in P2 - Hassan Haghighi; Mohammad Mosakhani; Mohammad Zaman Fashami (Annales Universitatis Paedagogicae Cracoviensis: Studia Mathematica, 2018)
Let Zn=p0+p1+...+pn be a configuration of points in P2, where all points pi except p0 lie on a line, and let I(Zn) be its corresponding homogeneous ideal in K[P2]. The resurgence and the Waldschmidt constant of I(Zn) in [5] have been computed. In this note, we compute these two invariants for the defining ideal of a fat point subscheme Zn,c= cp0+p1+...+pn, i.e. the point p0 is considered with multiplicity c. Our strategy is similar to [5].